Religion and Public Criticism: Dialogue for Reconsidering Religious Peace - Putri Nurfitriani; Naupal Asnawi (JURNAL ISLAM NUSANTARA, 2025)
Religious criticism is an integral part of a multicultural society, yet it can become sensitive amid debates over freedom of expression and religious respect. Recent cases, such as online disputes between preachers and the rise of ex-Muslim voices, demonstrate how religious criticism can strengthen dialogue or deepen divisions. This study aims to distinguish two contrasting forms of religious criticism in the contemporary public sphere: destructive criticism, which reinforces polarization and hostility, and dialogic criticism, which encourages transformation of understanding and increases tolerance between religious communities. The study adopts Mikael Stenmark’s framework of forms of religious criticism. It examines two influential cases: the Apostate Prophet, whose online content often shapes public perception through secular, confrontational criticism of Islam, and Husein Ja’far Al Hadar, a preacher whose inclusive and dialogic approach promotes tolerance. The study uses qualitative digital ethnography and discourse analysis to examine religious criticism in online media. The two contrasting figures were deliberately selected based on their distinct digital influence and communication styles. Data from YouTube dialogues and podcasts are analysed to identify patterns of constructive and destructive criticism. The findings suggest that dialogical criticism, which encourages understanding and tolerance, has greater potential to maintain interfaith harmony in Indonesia’s pluralistic society.